Evaluasi Deskriptif Umur Panen Melon (Cucumis melo, L) Di Pekanbaru - Surtinah Surtinah (Universitas Lancang Kuning, 2017)
The objective of the study was to examine the factors that caused melon harvesting age in Pekanbaru faster than in the melon-producing regions. The research method used is descriptive qualitative. The results of the discussion found that the factors that influence the harvesting age of melon in Pekanbaru City are the water stress condition, the unfulfilled essential ingredients, the insufficient planting medium of organic matter, the importance of growth regulators that can enlarge the fruit and maintain the age of the plant, environmental modification.